FORMULATION AND CHARACTERIZATION OF SUSTAINED RELEASE MATRIX TABLETS OF IVABRADINE USING 32 FULL FACTORIAL DESIGN - Kothiya, Olvishkumar M.; Patel, Bhavana A.; Patel, Kunal N.; Patel, Madhubhai M. (International Journal of Applied Pharmaceutics, 2018)
Objective: Ivabradine (IB) is anti-Ischemic drug and used for the symptomatic management of stable angina pectoris. IB acts by reducing the heart rate in a mechanism different from beta blockers and calcium channel blockers, two commonly prescribed anti-anginal drugs. IB has a short biological half-life and the dose of 5/7.5 mg twice a day. In this present study, an attempt has been made to prepare sustained release tablet of IB to achieve the desired drug release. Methods: The sustained release polymers, hydroxypropyl methylcellulose K100M (HPMC K100M), guar gum (GG) and xanthan gum (XG) were taken for the preliminary trail from which guar gum and xanthan gum had shown better drug release. Initially, drug-excipients compatibility studies were carried out by using Fourier transformed infrared spectroscopy (FTIR) and Differential Scanning Calorimetry (DSC) which showed no interaction between drug and excipients. Tablets were prepared by wet granulation technique and evaluated for pre-compression and post-compression parameters. Results: 32 full factorial design was applied to achieve controlled drug release up to 24 h. The concentration of GG (X1) and XG (X2) were selected as independent variables and the % CDR at 2 h. (Y1) and 18 h. (Y2) were taken as dependent variables. In vitro drug release study revealed that as the amount of polymers increased, % CDR decreased. Conclusion: Contour as well as response surface plots were constructed to show the effect of X1 and X2 on % CDR and predicted at the concentration of independent variables X1 (10 mg) and X2 (10 mg) for a maximized response. The optimized batch (O1) was kept for stability study at 40±2 °C/75±5 %RH for a period of 6mo according to ICH guidelines and found to be stable.